The value of international volunteers experience to the NHS - B. Zamora; M. Gurupira; M. Rodes Sanchez; Y. Feng; K. Hernandez-Villafuerte; J. Brown; K. Shah (BMC, 2019)
Abstract Background Global Engagement works with health partnerships to establish workforce and educational translation on a global scale to support the National Health Service (NHS). There is growing evidence on how international experiences (through volunteering, exchanges and placements) benefit the NHS through an innovative workforce that develops international best practice and promotes lifelong learning. Most of this evidence has been captured though surveys to returned international volunteers. However, there is limited evidence about how to quantify the value that returned international healthcare volunteers bring back to their country of residence. Methods This paper identifies the various benefits to the NHS from returned international healthcare volunteers. The outcomes from returned international volunteers, which have been identified as relevant form a NHS perspective, are linked to three key areas in a multisector analytical framework used by the World Bank to evaluate labour market programmes: (1) Investment climate and Infrastructure, (2) Labor market regulations and institutions, and (3) Education and skills development. The monetary value of these outcomes is quantified through productivity indices which capture the economic value that the achievement of these outcomes have on the quality of the NHS labor force. This model is applied to a dataset of international volunteers provided by the Global Engagement health partnerships. Results The results suggest that international volunteering generates average productivity gains of up to 37% for doctors and up to 62% for nurses. Average productivity gains estimated from health partnerships data vary depending on duration of volunteering periods and occupational category mix. Conclusions Our analysis offers a value for money rationale for international volunteering programmes purely from a domestic and NHS perspective. The valuation method considers only one of the aims of international volunteering programmes: the development of the existing and future NHS workforce. Broader benefits for health system strengthening at a global level are acknowledged but not accounted for. Overall, we conclude that if the acquisition of volunteering outcomes is realised, the NHS can accrue a productivity increase of between 24 and 41% per volunteer, with a value ranging from £13,215 to £25,934 per volunteer.